2005
DOI: 10.1369/jhc.5a6625.2005
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PDE11A in Normal and Malignant Human Tissues

Abstract: S U M M A R Y Cyclic nucleotide phosphodiesterase 11A (PDE11A) is the newest member in the PDE family. Although the tissue distribution of PDE11A mRNA has been shown, its protein expression pattern has not been well studied. The goal of this report is to investigate the distribution of PDE11A proteins in a wide range of normal and malignant human tissues. We utilized a polyclonal antibody that recognized all four PDE11A isoforms. Its specificity was demonstrated by Western blot analysis on a recombinant human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 30 publications
(53 reference statements)
1
40
0
Order By: Relevance
“…Recently, after running a wholegenome association study, we reported inactivating mutations of the phosphodiesterase 11A (PDE11A) in a subgroup of patients with primary pigmented nodular adrenocortical disease and other forms of bilateral hyperplasia (7). PDE11A is a dual-specificity phosphodiesterase; it is expressed in several endocrine tissues, including the adrenal cortex (8)(9)(10)(11)(12). The PDE11A gene was mapped to the 2q31-35 chromosomal region and the adrenal tumors from patients with PDE11A-inactivating mutations showed 2q allelic losses, although a cause-and-effect relationship could not be shown because the study was a loss-of-heterozygosity and association one (7).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, after running a wholegenome association study, we reported inactivating mutations of the phosphodiesterase 11A (PDE11A) in a subgroup of patients with primary pigmented nodular adrenocortical disease and other forms of bilateral hyperplasia (7). PDE11A is a dual-specificity phosphodiesterase; it is expressed in several endocrine tissues, including the adrenal cortex (8)(9)(10)(11)(12). The PDE11A gene was mapped to the 2q31-35 chromosomal region and the adrenal tumors from patients with PDE11A-inactivating mutations showed 2q allelic losses, although a cause-and-effect relationship could not be shown because the study was a loss-of-heterozygosity and association one (7).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the brain, initial studies failed to identify PDE11A mRNA in samples from an entire brain or whole brain regions (3,4). This failure is not surprising, given that a later study employing immunohistochemistry reported sporadic, low levels of expression in "neurons" and "glia" [brain region not identified (11)]. If PDE11A is expressed only in a subpopulation of cells within a discrete subregion of the brain, one might not expect to detect expression when analyzing samples prepared from an entire brain (region).…”
mentioning
confidence: 99%
“…Slides were deparaffinized, hydrated, and processed for routine IHC as previously described (D'Andrea et al 2005;D'Andrea et al 2000). Briefly, slides were microwaved in Target buffer (Dako, Carpinteria, CA), cooled, placed in distilled H 2 O, and then treated with 3.0% H 2 O 2 for 10 min.…”
Section: Immunohistochemistrymentioning
confidence: 99%